Pedagogy of Progress and the Meta-function of Philosophy as a Worldview - Nowak, Andrzej W. (Sensus Historiae, 2023)
This paper is intended to show how the worldview function of philosophy evolved. This particular function played a significant role during the communist period, where it was part of the legitimation of the political system; after 1989 there was a retreat from such a view of philosophy. Indicating the negative consequences of neo-liberal hyper-normalization and the accompanying “capitalist realism,” the text points to the need to recover the potential associated with the worldview function of philosophy.